Statistics on Differences in the Institutional Composition of the National Economy and Issues Related to its Harmonization - O. V. Morozov; A. G. Biryukov; M. A. Vasiliev (Статистика и экономика, 2020)
This article focuses on the assessment of the size of the public sector, which goes back to the assessment of the degree of state participation in the domestic economy and remains controversial. Such assessments are often carried out without the presentation of threshold criteria and without evaluation of its effectiveness and combination with other institutional sectors. At the same time, it is obvious that the ratio between the public and other (non-state) sectors refers to the issue of strategic importance, to the issue of the effectiveness of the country's economic system in its integrity, and therefore requires theoretical, methodological and practical resolution.The objectives of the research are: (1) to determine the relative scale and efficiency of the public sector functioning in the national economy, to establish minimum necessary and maximum possible values of its scale; (2) to determine the size and establish a measure of harmonious combination of institutional components of the domestic economy aimed at maximizing its efficiency.Materials and methods. Theoretical foundations of the research have been developed on the basis of the authors' preferences regarding the results of conceptual and applied developments of domestic scientists in the field of philosophy, mathematics, economics and sociology, as well as the practice of structural and spectral analysis in their subject areas. The analysis of parameters (indicators) of the state and other institutional sectors of the national economy was carried out (mainly) on the basis of statistical data of ROSSTAT for 2006-2016, materials of official reports and developments of analytical centers. The methodological basis of the research is formed by works on modular theory of society, public sector economy, and structural harmony of systems. Tabular methods of visualization of research results and statistical methods of source data processing were used. Standard packages of Microsoft Office application programs were used for solving research tasks.Results. It is shown that against the background of a decrease in relative resource capacity, the public sector over the period under review does not show an increase in the degree of government participation in the Russian economy. At the same time, performance indicators of the public sector did not show not only worse, but also worsening values, both as compared with the private sector and the economy as a whole. Criteria of minimum required and maximum possible scale of the public sector have been defined and it is shown that as of 2016 the integral indicator of the scale of the public sector of the Russian economy does not reach the minimum required value. A quantitative model for optimizing the sectoral composition of the national economy has been constructed. System solutions are proposed and a method for determining the share of institutional sectors in the structure of the national economy is given.Conclusion. The article deals with the issues of state participation in the economy, defines the scale and efficiency of the public sector in the national economy. It is noted that within the limits of maximally liberal and maximally ethical ideological statements the task of optimization of neither the size of the public sector of the national economy nor the harmonious combination of its sectoral composition find a satisfactory solution. The analysis of institutional composition of the national economy has been carried out and the way of optimization of its structure has been shown, the direction of the state economic policy on optimization of institutional structure of the national economy has been determined. Orientation of economic policy towards achievement of optimal structure (harmony) of economic system (as well as the very movement towards it) will create conditions not only for increase of its efficiency, but also will allow to satisfy economic needs of socially-professional groups to the fullest extent, and society as a whole will successfully develop.